Professionality of Public Primary School Teachers in West Praya District, Central Lombok District - Marzuki; Fahruddin; Sudirman (International Journal of Scientific Multidisciplinary Research, 2024)
The research is motivated by the need to develop the professional competence of teachers in elementary schools so that the quality of the teachers concerned can continue to be maintained and even improved. The research aims to describe the professional competence of teachers in elementary schools. The research method is qualitative descriptive research. Respondents totaled 11 teachers with a composition of 3 male teachers and 8 female teachers. Stages of pre-field research, field research, and data analysis. The research results show that the professional competence of teachers in elementary schools is in the medium category. Maximum efforts are needed to continuously improve the professional competence of elementary school teachers so that the professional competence of the teachers concerned can be maintained and even improved. The professional competence of elementary school teachers can be developed through periodic optimization of teacher work groups and mastery of technology and information skills